(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
Here, the theme of body expression is focused on the notion of harmonic work between body, sound and word in the formation of artists of the scene. In this interdisciplinary approach, we list the founding principles of body expression, revealing that sounds and voice are components of this practice. We present Klauss Vianna as an introducer of corporal expression in Brazilian theater and use as a point of analysis for this interdisciplinary dialogue the Body-Sound-Word course offered by Vianna, Sideny Miller and Paulo Afonso Grisolli in the 1970s in Rio de Janeiro, which leads us to understand how a course from the last century can help us to reformulate our recent practice.